Breeding tepary bean (Phaseolus acutifolius) for drought adaptation: A review. (24th January 2020) - Mwale, Saul Eric; Shimelis, Hussein; Mafongoya, Paramu; Mashilo, Jacob
Abstract: Tepary bean ( Phaseolus acutifolius A. Gray ) is a relatively higher drought‐tolerant crop than common bean ( P. vulgaris ), serving as genetic resource for food and genetic enhancement of related legumes. Tepary bean production is hampered by cultivation of low yielding and abiotic stress‐susceptible cultivars. Targeted selection of agronomic, physiological and biochemical traits that maximizes yield gains using Phaseolus gene pool is useful to develop stress‐tolerant and high‐performing genotypes. The objective of this review is to provide breeding progress made regarding tepary bean improvement for drought adaptation. Agronomic, physiological and biochemical traits utilized for selection of drought‐tolerant genotypes are highlighted. Genetic and genomic resources developed for tepary bean or closely related species such as common bean useful for genetic analysis and breeding are discussed. Opportunities and challenges to facilitate breeding of tepary bean genotypes with improved abiotic stress adaptation are highlighted. This will enable development of drought‐tolerant tepary bean genotypes targeting selection of agronomic, physiological and biochemical traits. Use of genetically related and complementary Phaseolus species and marker‐assisted selection method is key to developing drought‐tolerant genotypes.